DESIGN OF STATE-DERIVATIVE FEEDBACK CONTROLLERS USING A STATE FEEDBACK CONTROL DESIGN - Cardim, Rodrigo [UNESP]; Teixeira, Marcelo C.M. [UNESP]; Assunção, Edvaldo [UNESP]; Covacic, Márcio R. [UNESP] (Elsevier, 2007)
A simple method for designing a state-derivative feedback gain and a feedforward gain such that the control law is equivalent to a known and adequate state feedback and reference feedforward control law is presented. It is assumed that the plant is a linear controllable, time-invariant, Single-Input (SI) or Multiple-Input (MI) system. This procedure allows the use of well-known state feedback design methods to directly design state-derivative feedback control systems. The state-derivative feedback can be useful in the control of mechanical systems, using accelerometers as sensors. Three examples considering the pole-placement and decoupling problems illustrated the proposed method.
Keywords: Decoupling Problem; Eigenvalue Placement; Linear Multi-Input (MI) Systems; Pole Assignment; State Feedback; State-Derivative Feedback